Murder and Aesthetics in Patricia Highsmith’s Deep Water - Robert Lance Snyder (European Journal of American Studies)
Patricia Highsmith’s fifth novel, Deep Water (1957), revolves around three murders committed by 36-year-old Victor Van Allen, head of Greenspur Press in Little Wesley, Massachusetts, and a genuine aesthete whose interests include handset colophons, snails, bee culture, carpentry, music, painting, stargazing, and gardening. An esteemed non-conformist in an upscale New England community, Van Allen is initially tolerant of his wife’s serial infidelities but reaches a breaking point when he kills two of her lovers before strangling his spouse. Highsmith’s mordantly unsettling narrative anticipates the mimetic fascination with murder in postmodern popular culture that ever since Thomas De Quincey’s 1827 satirical essay on the subject has abounded in fiction, nonfiction, and film. Writing against the grain of post-World War II conformism, Highsmith proleptically addresses issues of maladaptation in her portrait of a repressed sociopath who attempts to mask his inner rage via the sublimation of aesthetic pursuits.